2014
DOI: 10.1007/jhep11(2014)076
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of large N factorization in CFT4: exploring bulk spacetime in AdS5

Abstract: Large N factorization ensures that, for low-dimension gauge-invariant operators in the half-BPS sector of N = 4 SYM, products of holomorphic traces have vanishing correlators with single anti-holomorphic traces. This vanishing is necessary to consistently map trace operators in the CFT 4 to a Fock space of graviton oscillations in the dual AdS 5 . We investigate the regimes at which the CFT correlators do not vanish but become of order one in the large N limit, which we call a factorization threshold. Quite ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(117 reference statements)
1
3
0
Order By: Relevance
“…For us it is a choice that tells us how big of an error we should allow. A similar (slightly weaker) limit is obtained from three point functions [30] (see also [31] and references therein for earlier work on the exact three point functions).…”
Section: Cutoff Physics In the Young Tableaux Formalismsupporting
confidence: 55%
“…For us it is a choice that tells us how big of an error we should allow. A similar (slightly weaker) limit is obtained from three point functions [30] (see also [31] and references therein for earlier work on the exact three point functions).…”
Section: Cutoff Physics In the Young Tableaux Formalismsupporting
confidence: 55%
“…Regarding previous work, non-local effects in quantum gravity have been proposed by several authors, most notably Giddings [23,24,25], and mechanisms for the breakdown of bulk locality in AdS/CFT have been studied in [26,27]. Many of the results in this paper build on the ideas presented in [28,29].…”
Section: Introductionmentioning
confidence: 65%
“…The complex matrix model correlator can be calculated by using character sums. In [26], it is shown that…”
Section: The Complex Matrix Modelmentioning
confidence: 99%